PENGARUH AKUMULASI KEPERCAYAAN DAN PERSEPSI UMPAN BALIK TERHADAP RETENSI PELANGGAN MASKAPAI PENERBANGAN LION AIR PASCA PEMULIHAN LAYANAN - Fadhlul Husni, Mukhlis Yunus (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
Competition in business aviation services is very tight and vulnerable to the issue of trust. Competition is done with a variety of strategies with the goal of customer retention. This study aims to determine the effect of accumulative trust and customer’s perception of feedback to impulsive customer’s retention in the Lion Air post – service recovery. This research method using questionnaires as research instruments. The sample of research are 200 customer was taken by purposive sampling methods with the criteria that respondents who had experienced customer service failure in the Lion Airline least one and not the civilian apparatus of official travel for state or private employees, and the respondent is a decision maker. Structural Equation Modelling-Partial Least Square used as a method of analysis to determine the effect of the variables involved. The results showed that the accumulative trust and customer’s perception of feedback effect on customer’s retention and service recovery satisfaction, Better the accumulative trust and customer’s perception of feedback, higher customer’s retention and service recovery satisfaction. Service recovery satisfaction also affects on  customer retention. The existence of service recovery satisfaction can be mediating variable between accumulative trust and customer’s perception of feedback with customer’s retention.  Keywords: Accumulative Trust, Customer’s Perception of Feedback, Service Recovery Satisfaction, Customer’s Retention